The Impact of Audit Reports on Financial Information Content - Vaziri, Alireza; Azadi, Kayhan (International Journal of Economics and Financial Issues, 2017)
Investors fund in order to access to more wealth. Financial information of companies is one of the important factors considered by investors in making decision. According to accounting standards, the major goal of providing forms and financial reports is providing useful information about financial position and the results of operations of commercial unit for user decision making. Several factors influence on financial information provided by companies. One of these factors can be audit reports. Therefore, major goal of this research is investigating the effects of audit reports on financial information reported in Tehran Stock Exchange. Method of this research is practical in goal and is descriptive in type. The types of auditor and auditor’s assessment (audit organizations or institutions) were proposed as independent variables and financial information (stocks return) was proposed as dependent variable. In this research 117 accepted companies in Tehran Stock Exchange during 2009-2014 were selected as statistical sample. Research hypotheses were tested by fitting of linear regression models of combined data. The results showed that the type of auditor and auditor’s assessment have a significant relationship with stocks return (financial information). Keywords: The Type of Auditors, Stocks Return, The Type of Auditor’s Assessment, Tehran Stock Exchange JEL Classifications: E44, M42